2010
DOI: 10.1007/s11525-010-9184-z
|View full text |Cite
|
Sign up to set email alerts
|

Verbal morphology in Murrinh-Patha: evidence for templates

Abstract: If questions concerning affix ordering are among the central ones in morphological theory, then languages with templatic morphology appear to provide the least interesting answer, since in these languages affix order must be simply stipulated in the form of arbitrary position classes. For this reason, much recent research into templatic morphology has attempted to show that affix order in such languages is in fact governed by underlying semantic or syntactic principles. The most fully articulated position in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Courtney and Saville-Troike (2002) suggested that morphological factors drive the acquisition of Quechua and Navajo, with roots/stems being extracted in early verb forms irrespective of their perceptual salience. This raises the interesting question of what children do when the root/stem is discontinuous in the verbal word, as in the Australian language Murrinh-Patha (Nordlinger 2010). 9 Secondly, morphological complexity does not always lead to acquisitional complexity.…”
Section: Resultsmentioning
confidence: 99%
“…Courtney and Saville-Troike (2002) suggested that morphological factors drive the acquisition of Quechua and Navajo, with roots/stems being extracted in early verb forms irrespective of their perceptual salience. This raises the interesting question of what children do when the root/stem is discontinuous in the verbal word, as in the Australian language Murrinh-Patha (Nordlinger 2010). 9 Secondly, morphological complexity does not always lead to acquisitional complexity.…”
Section: Resultsmentioning
confidence: 99%
“…In the stratal account of Murrinhpatha, it is shown that PWords have distinct effects in stem formation and phrasal phonology. This analysis builds on previous work on the morphological structure of the Murrinhpatha verb (Blythe 2009;Mansfield 2015Mansfield , 2016bNordlinger 2010Nordlinger , 2015Street 1987;Walsh 1976), but in the light of insights provided by prosody, proposes a revised description of the morphology. The main revision proposed is to replace a purely morphotactic "template" morphology with a mixture of prosodic constituency and morphotactics.…”
Section: Introductionmentioning
confidence: 84%
“…If we distinguish those bound elements which realise obligatory grammatical categories such as tense, agreement/argument indexing, case, noun class , and number, then the class of affi xes is relatively small and coherent in NPN languages: it consists just of these grammatical category-realising elements. Templates run into problems in the (unusual) cases where alternative orders of bound morphemes are possible, as in, for example, Murrinh-Patha (Nordlinger 2010), Arrernte (Henderson 1998(Henderson : 216, 2002 and Rembarrnga (McKay 19 75: 92). Some bound stems behave as "true" (phrasal) clitics (Zwicky 1985), in that they attach to words outside the last affi x.…”
Section: Word Structure and Polysynthesismentioning
confidence: 99%